Economic losses associated with respiratory and helminth infections in domestic pigs in Lira district, Northern Uganda - Oba, Peter; Dione, Michel; Mwiine, Frank N.; Wieland, Barbara; Erume, Joseph; Ouma, Emily (Frontiers in Veterinary Science, 2023)
This study sought to quantify direct economic losses due to respiratory and gastrointestinal (GI) helminth infections in domestic pigs in Uganda. In a longitudinal study design with repeated measures, farm visits were made at 2-month intervals from October 2018 to September 2019. Weaner and grower pigs (n=288) aged 2-6 months from 94 farms were sampled. The pigs were monitored for growth and screened for exposure to four important respiratory pathogens: porcine circovirus type 2 (PCV2), porcine reproductive and respiratory syndrome virus (PRRSv), Mycoplasma hyopneumoniae (M. hyo), Actinobacillus pleuropneumoniae (App) using ELISA tests. Farm management practices were recorded and used to generate management level scores. Treatment expenses incurred were recorded throughout the study. A mixed effects model was fitted to quantify effects of respiratory and helminth infections on average daily weight gains (ADGs), with farm as a random effect. Analysis of variance (ANOVA) was used to establish differences in mean treatment costs by farm management standard. Financial losses were estimated from average carcass dressing percentage, ADG reductions during fattening (200 days). Results showed a grower pig in a given farm exposed to PRRSv and Ascaris spp had significantly lower ADG by 21.2 and 26.0 gr/pig/day respectively, compared to a similar unexposed pig (p<0.05). Mean treatment costs per pig declined significantly with increase in management standard scores (MSS), from USD 1.13 per pig in MSS 1 (poor management) farms to USD 0.95 for MSS 3 (better management) farms (p<0.05). We show that monetary losses due to PRRSv and Ascaris spp. infection amounted to USD 8.2 ± 3.7 and 10.0 ± 5.9 (Mean ± SEM), respectively per pig during fattening. This study strengthens evidence that improving management practices to reduce infections mitigates economic losses. To guide interventions, further studies are required to unravel the full extent of indirect economic losses.